(untitled) (American Journal of Islam and Society, 2012)
In the last three decades Islam has reemerged as an important global phenomenon and is aptly referred to as a contemporary Islamic revivalism. As a phenomenon, contemporary Islamic revivalism is an attempt by a small but important section of the Ummah (community of believers) to reestablish Islam as the principal paradigm for personal as well as public life across the globe. Its hallmark is a return to Islamic origins, the fundamentals of the authentic faith embodied in the Qur’ān and the Sunnah, the sayings and practices of the Prophet Muḥammad (ṢAAS). This article is an exploration of the explanations of a contemporary Islamic revivalism. Contemporary Islamic revivalism can be explained in many different ways, however, this paper focuses on the crisis perspective, the success perspective, and the crisis of modernity perspective to arrive at a more analytical understanding of this important sociological phenomenon.